Employee Perceptions of Human Resources Information Systems, Attitude, and Payroll Effectiveness in Uganda’s Public Service - Frances Tereza Athieno; Seperia Bwadene Wanyama; Samuel Eyamu (Compensation & Benefits Review, 2026)
Human Resource Information Systems (HRIS) are central to payroll administration, yet payroll inefficiencies persist despite substantial investment in digital technologies. This study examined how employees’ perceptions of HRIS—perceived usefulness and perceived ease of use—and employee attitudes influence payroll effectiveness in Uganda’s public service. Data were collected from 100 users of the Integrated Personnel and Payroll System (IPPS) and Human Capital Management System (HCMS) across the Ministry of Public Service, three government universities, and seven local governments. The findings show that perceived usefulness, perceived ease of use, and positive employee attitudes improve payroll effectiveness by enhancing the accuracy, timeliness, and reliability of payroll administration. Employee attitude partially mediates the relationship between perceived usefulness and payroll effectiveness but does not mediate the relationship between perceived ease of use and payroll effectiveness. The study extends the Technology Acceptance Model to mandatory public-sector HRIS and highlights the importance of user-centred system design, training, and change management.